ANALYSIS OF THREATS TO WEBSITES AND THEIR PROTECTION - Mahkamov Anvarjon Abdujabborovich; Tuhtanazarov Dilmurod Solijonovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. The article presents the current threats to websites and ways to protect them, outlining measures to ensure information security. It emphasizes the implementation of modern technologies to protect communication networks, software products, information systems, and resources. Additionally, it discusses the development of technical infrastructure to further enhance the protection of information resources.